Meningkatkan Hasi Belajar Bahasa Indonesia Materi Menuliskan Kembali Isi Dongeng Menggunakan Media Audio Visual Pada Peserta Didik Kelas III SD Katolik Wegoknatar Kecamatan Hewokloang - Ignasia Bergita; Lukas Bera; Maria Angelina Fransiska Mbari (Departement of Mathematics Education, 2023)
This tudy aimed to improve learning outcomes to rewrite the content of fairytales using audio-visual media for grade III students at SDK Wegoknatar. This research employed classroom action research (CAR) designed to assist teachers (researchhers) in finding and solving learning problems that occur in class. This classroom action research was conducted in cycles, between cycle I and cycle II. The sample was 16 students. The result pointed out that after giving action for two cycles, the everage score of the test result of improving learning outcomes in rewriting the content of fairy tales using audio-visual media in the indonesian languege subject had increased. The frist meeting of Cycle I resulted in a score of 43.7% and the second meeting 62,5% meaning that not fullfilled the KKM. In the frist meeting of cycle II, the score increased by 87,5% and at the second meeting by 100% which also increased by 100%. The results implied that improving learning outcomes in rewriting fairy tales using audio-visual media in Indonesian subjects can be further applied to improve students’ learning achievement, especially in Indonesian language subjects.